Case Study of the Differences and Similarities between Continental Dishes and Local Dishes (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to examine the differences and similarities between continental and local Indonesian cuisine, focusing on the case studies of Beef Stroganoff and Rendang. The study covers aspects such as ingredients, cooking techniques, presentation, and the cultural values embedded in these dishes. The research employs a qualitative descriptive case study approach, collecting data through observation, interviews, and literature review. The results indicate that continental cuisine emphasizes the use of high-quality ingredients, often favoring simplicity and freshness, and applies quick cooking techniques such as sautéing or grilling. Presentation is also a key element, with attention to aesthetic appeal and portion control. Beef Stroganoff, for example, is known for its creamy texture and elegant plating. In contrast, local Indonesian cuisine, as exemplified by Rendang, is characterized by its complex spice blends and slow cooking methods, often taking hours to achieve the desired taste and texture. Rendang holds deep social and cultural meanings, commonly served at ceremonial events or traditional gatherings, symbolizing patience, generosity, and respect for tradition. Despite these differences, both types of cuisine share similar functions in society: they both aim to fulfill nutritional needs, express cultural values, and strengthen social bonds. Food, in both contexts, becomes more than just sustenance—it is a form of identity and communication. This study recommends integrating local culinary studies into the culinary education curricula, especially at vocational and higher education levels. By doing so, students not only learn technical skills but also develop an appreciation for the cultural heritage embodied in Indonesian cuisine. This is essential in the era of globalization, where local identities risk being overshadowed by global culinary trends. Preserving and promoting traditional dishes like Rendang is vital for safeguarding Indonesia’s gastronomic identity and fostering pride in national culture.